Evaluation of the antiproliferative effect of selected plant extracts on colon and skin cancer cell lines - Sawsan Atallah Oran, Israa Yousef, Sahar Majdi Jaffal (Journal of Applied Pharmaceutical Science, 2022)
The aim of this study was to assess the antiproliferative effect of extracts obtained from medicinal plants that grow wild in Jordan against the human melanoma (WM136-1A) and colon cancer (Caco-2 cancer) cell lines using fibroblast cell lines as control cells. The selected plants are Varthemia iphionoides (Asteraceae), Micromeria myrtifolia (Lamiaceae), Micromeria nervosa (Lamiaceae), Origanum dayi (Lamiaceae), Ajuga chia (Lamiaceae), Salvia palaestina (Lamiaceae), and Bongardia chrysogonum (Berberidaceae). The results showed that M. nervosa and O. dayi exhibited antiproliferative activity against Caco-2 cancer cell line, with half-maximal inhibitory concentrations (IC50) that equal 98 ± 2.5 and 73.6 ± 3.4 μg/ml, respectively. Furthermore, A. chia, B. chrysogonum, and O. dayi exhibited antiproliferative activity against the WM136-1A cancer cell line, with IC50 that equals 400 ± 5.1, 98.1 ± 3.2, and 245 ± 3.6 μg/ml, respectively. None of the extracts had an effect on fibroblast cells at any used concentration. In conclusion, the extracts of M. nervosa, O. dayi, A. chia, and B. chrysogonum showed promising antiproliferative potential and can be good candidates for the development of novel anticancerous agents.
Keywords: Ajuga chia, Micromeria myrtifolia, Micromeria nervosa, Origanum dayi, Salvia palaestina, Varthemia iphionoides, Bongardia chrysogonum, antiproliferation